DESIGN AND FINITE ELEMENT NUMERICAL STUDY OF SOFT SOIL IMPROVEMENT BEHAVIOR MODEL USING VACUUM PRELOADING - Aulia Is Marsa, Nisrina
Buildings constructed at land whose Jenis Tanah is soft will face the probability of excessive soil settlement for the long duration. This problem can be handled by improving the soil which one of the effective methods is installing Prefabricated Vertical Drain (PVD). PVD is used to shorten the consolidation settlement time needed and to burden the soil with loads heavier than construction loads. One of the soft soil loading methods is vacuum preloading. Suction occurred because of the vacuum will displace the soil inward. This method is different from embankment preloading which cause shear failure to the soil. In this research, soil improvement plan includes dimensions, lengths, and spacings of the PVD based on the soil parameters and the installation of the vacuum on the site. Different lengths and spacings design of PVD effects will be evaluated on soil consolidation rate. Soil behavior after the improvements are applied will also be examined. The research is conducted by modelling some cases of vacuum with variation of pressure magnitudes and distributions on finite element software PLAXIS 2D. The modelling results of soil settlement, excess pore pressure, and pore water pressure will be compared with the field monitoring data given